2022
DOI: 10.1039/d2py01104b
|View full text |Cite
|
Sign up to set email alerts
|

Silica gel supported ionic liquids as effective and reusable catalysts for the synthesis of highly reactive polyisobutylene in non-polar media

Abstract: Silica gel supported catalysts based on FeCl3 and AlCl3 as well as chloroaluminate and chloroferrate ionic liquids have been synthesized and tested in cationic polymerization of isobutylene. Among them, supported...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 78 publications
(190 reference statements)
1
10
0
Order By: Relevance
“…It can be speculated that if toluene macrocation stabilization and chain transfer indeed occur, peaks associated with toluene might become evident in the 1H‐NMR spectra of the respective materials, which has not been observed in the obtained data. Berezianko et al reported an increase in monomer conversion when toluene was used as a solvent, instead of n ‐hexane, to solubilize the catalyst 16 . Other authors observed that monomer conversions decreased in nonpolar solvents, corroborating the results found in the present work.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…It can be speculated that if toluene macrocation stabilization and chain transfer indeed occur, peaks associated with toluene might become evident in the 1H‐NMR spectra of the respective materials, which has not been observed in the obtained data. Berezianko et al reported an increase in monomer conversion when toluene was used as a solvent, instead of n ‐hexane, to solubilize the catalyst 16 . Other authors observed that monomer conversions decreased in nonpolar solvents, corroborating the results found in the present work.…”
Section: Resultssupporting
confidence: 91%
“…It must be observed that toluene is capable of stabilizing the propagating species, which results in a decrease in the instantaneous concentration. This allows a suitable equilibrium between dormant and active species, while suppressing side reactions and favoring 𝛽‐proton abstraction by counterions, thus, leading to the formation of exo‐olefin bonds 16,19,33 . As also noted previously, addition of ether products with lower average molar masses and better heat exchange in the medium, enables higher chain transfer and desirable polymeric microstructure.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Heterogeneous catalysis of polymerization is a promising approach for industrial production due to its advantages of easy separation and reusability, which is more environmentally friendly and economically benign compared to homogeneous catalysis. , In recent years, heterogeneous catalysis for reversible deactivation radical polymerization (RDRP), e.g., reversible addition–fragmentation chain transfer (RAFT) polymerization , and atom radical transfer polymerization (ATRP), , has gained more and more attention. Elegant works have been demonstrated using various heterogeneous catalysts, such as semiconductors, , metal–organic frameworks, quantum dots, carbon dots, composite materials, conjugated polymers, nanocomposites, and self-assembly catalysts. While heterogeneous catalysis has shown promise in various polymerization techniques, it remains limited in the case of living cationic polymerization (LCP), which enables the synthesis of well-defined polymers with controlled molecular weights, narrow molecular weight distributions (MWDs), precise composites, and complex architectures. Although some heterogeneous catalysts for cationic polymerization have been reported, few have achieved living/controlled polymerization. In 2007, Kanazawa et al reported the first case of heterogeneously catalyzed LCP by using Fe 2 O 3 as a heterogeneous catalyst with an extra base . Subsequently, the same group screened a variety of metal oxides as heterogeneous catalysts for LCP, , providing alternatively types of initiating systems.…”
Section: Introductionmentioning
confidence: 99%